Faktor-Faktor Yang Mempengaruhi Kinerja Pejabat Pengelola Keuangan Skpd Pemerintah Kota Surakarta - Susanto, Arya Bima; , Dr. Zulfikar, SE, M.Si (2016)
This study aimed to examine the effect of budgetary participation , the characteristics of accounting information , public sector accounting , organizational motivation , information technology and organizational culture on the performance of financial management officer . Based on the results of the study are expected to provide an overview of the dynamics that occur in SKPD Office of Surakarta in particular its financial management officer . This research included in this type of quantitative research by using direct survey through questionnaires . The population in this study is a financial management officer who worked in the Office of SKPD in Surakarta . Techniques used in sampling is purposive sampling method. Collecting data using questionnaires that have been tested for validity and reliability levels . Data were analyzed using multiple regression analysis , F test , coefficient determination test , t test , and classical assumption . The results showed that: (1) Participation of the budget affect the performance of financial management officer, the t test was obtained thitung 2,716 and 0,011 significance value <0.05. (2) the characteristics of accounting information on the performance of financial management officer. Evident from the t test to obtain the results and significance thitung 2,150 0,040 <0,05. (3) public sector accounting effect on the performance of financial management officer, of the t test results obtained thitung 2,856dan significance of 0.008 <0.05. (4) Motivation affect the performance of the organization's financial management officer, on the count of 2,258 t test and values sig 0.032 <0.05. (5) information technology affect the performance of financial management officer, of the t test obtained t calculate equal to 2.357 and sig 0.025 <0.05 (6) organizational culture affect the performance of financial management officer, of the t test obtained t calculate equal to 2,920 and sig 0.025 <0.05.